Predisposing risk factors for isolated bile leakage after pancreaticoduodenectomy - Aydin, Hüseyin Onur; Soy, Ebru Hatice Ayvazoğlu; Kirnap, Mahir; Moray, Gökhan (Annali Italiani di Chirurgia, 2023)
AIM: Isolated bile leakage (IBL) from hepaticojejunostomy, following pancreaticoduodenectomy, is a serious complication that increases morbidity and mortality. We aimed to assess the frequency of IBL development after pancreaticoduodenectomy and its underlying factors. MATERIALS AND METHODS: Patients who underwent pancreaticoduodenectomy for pancreatic diseases between January 2005 and January 2016 were retrospectively evaluated. Patients were dichotomized according to those with and without postoperative IBL. RESULTS: In the 111 patients who underwent pancreaticoduodenectomy during our study period, 8 patients (7.2%; 5 men/3 women) developed IBL. Risk of IBL development was significantly elevated among male patients, those with preoperative serum albumin < 3.5 g/dL, and those with previous cholangitis (P < 0.05). DISCUSSION: Male sex, preoperatively low levels of serum albumin, and preoperative history of cholangitis can be listed as risk factors for IBL development. Physicians should pay attention to the risk of postoperative IBL development in such patients.